FLUID FLOW THROUGH ROUGH FRACTURES IN ROCKS I: HIGH RESOLUTION APERTURE DETERMINATIONS - Isakov E.; Ogilvie S.R.; Taylor C.W.; Glover P.W.J. (My University, 2001)
Full characterisation of rough fracture surfaces and the resulting variable apertures is an important step in the drive towards an improved understanding of the factors which control fluid flow through rocks. A number of surface profiling techniques exist, such as needle or laser profiling. However, these techniques are difficult and time consuming to apply to the total area of a fracture because they involve measuring a large number of parallel profiles, which are then difficult to align accurately. Hence, although a single profile may have high resolution in the z-direction and the direction of the profile, the fracture surface has a much lower resolution due to alignment errors. We have developed and improved considerably a previously existing optical concept for obtaining the topography of a fracture surface where the information about surface heights is measured simultaneously. The method relies on the construction of high fidelity transparent models of the fracture surface, which are imaged while covered with dyed and undyed water. The resulting images are converted to topography by a simple calibration procedure that makes use of the Lambert-Beer law. This method utilises in-house OptiProf# software, which provides considerably more control over the imaging process than previous attempts at optical profiling. We have applied the technique to a range of rock fractures and test pieces, and have found the technique to work reliably, with lateral resolutions of 15 μm, and a vertical resolution of 15 μm, although all these could be improved by increasing the pixel count and the bit-depth of the camera, respectively.
Keywords: FLUID DYNAMICS; FRACTURES; ROCKS; IMAGE ANALYSIS; PHYSICAL MODELS